2019
DOI: 10.5005/jp-journals-10071-23178
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Outcome of Dengue Fever in Multidisciplinary Intensive Care Unit of a Tertiary Level Hospital in India

Abstract: Background India is one of the seven identified countries in South-East Asia region regularly reporting dengue fever (DF)/dengue hemorrhagic fever (DHF) outbreaks. Even though the dengue prodrome and evolution of illness are most often similar in many patients, progress and outcome may differ significantly depending on the severity of illness as well as treatment instituted. We studied the clinical manifestations, outcome and factors predicting mortality of serology confirmed dengue fever cases ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Depletion of intravascular volume leads to features of shock and hypoperfusion of various organs, instituting a cascade of hypoxic injury in various organ systems leading to shock and multi-organ dysfunction, which is a frequent cause of death in dengue [ 18 ], as also seen in our study. Multiorgan dysfunction syndrome particularly ARDS and AKI, were accompanying factors in most cases of dengue deaths in our study and they have been shown to be strong predictors of mortality in non-pregnant patients with dengue [ 19 ]. Therefore, organ dysfunction in pregnant women with dengue requires vigilant monitoring and intensive management in ICU, to salvage such women.…”
Section: Discussionmentioning
confidence: 98%
“…Depletion of intravascular volume leads to features of shock and hypoperfusion of various organs, instituting a cascade of hypoxic injury in various organ systems leading to shock and multi-organ dysfunction, which is a frequent cause of death in dengue [ 18 ], as also seen in our study. Multiorgan dysfunction syndrome particularly ARDS and AKI, were accompanying factors in most cases of dengue deaths in our study and they have been shown to be strong predictors of mortality in non-pregnant patients with dengue [ 19 ]. Therefore, organ dysfunction in pregnant women with dengue requires vigilant monitoring and intensive management in ICU, to salvage such women.…”
Section: Discussionmentioning
confidence: 98%
“…Among the dengue positive cases, 593 (60.9%) were male and 381 (39.1%) were female. The mean age among positive cases was 31 Month wise distribution of dengue cases showed the occurrence to be high during May to November with maximum in the month of August (Figure -1).…”
Section: Resultsmentioning
confidence: 99%
“…Other study shows that erythema, morbilliform rash, cutaneous hypersensitive reactions as atypical presentations of dengue (30). Infections caused by typhoid bacilli, leptospira, enterovirus with fever and gastro intestinal symptoms may simulate dengue fever (31).…”
Section: Discussionmentioning
confidence: 94%
“…16 Padyana et al found gall bladder wall edema in 44% of their cases on ultrasonography. 21 The authors suggest that ultrasound features of thickened gall bladder wall, pleural effusion, and ascites in a febrile patient should strongly favor the diagnosis of DF.Complications encountered in our cases included bleeding in 44 (10.29%), ARDS in 7 (1.67%), myocarditis in 6 (1.44%), seizures in 6 (1.44%), hemarthrosis in 1 (0.24%), and encephalopathy in 1 (0.24%) patient. Patil has reported altered sensorium & convulsions as neurological complications.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The clinical profile of dengue revealed fever as the most common presenting symptom (99.76%), as also substantiated by Chan et al, Fujimoto and Koifman et al, Kauser et al, Mandal et al, Imam and Prashanth, Jayadas et al, and Padyana et al who have reported fever in 99.7, 79.8, 100, 100, 98.3, 100, and 94.8% of their patients, respectively. 13,14,[17][18][19][20][21] Other presenting symptoms were vomiting and pain abdomen that can be due to liver injury caused by the dengue virus. 14 It is imperative to remember that other infections that cause fever and gastrointestinal symptoms such as typhoid, leptospirosis, enteroviral infections are common in India and may often lead to a delay in diagnosis of dengue.…”
Section: Discussionmentioning
confidence: 99%